STRENGTHENING THE ROLE OF BAWASLU IN ELECTION LAW ENFORCEMENT: SHOULD IT BE? - Al-Fatih, Sholahuddin (Faculty of Law Atma Jaya Yogyakarta University, 2025)
This article examines the ways to strengthen the Bawaslu role in Indonesian Election. The Election Supervisory Agency (Bawaslu) is a body authorized to oversee the enforcement of election laws, as mandated in Article 1 Number 17 of Law Number 7 of 2017 concerning Elections. In each electoral cycle, Bawaslu receives and registers thousands of cases. However, its role remains limited to supervision rather than adjudication. This restricted authority has hindered the effective resolution of many alleged election violations. This article presents the findings of juridical-normative research employing a statute approach, case approach, and conceptual approach. It addresses two central problems: (1) the challenges in enforcing election law in Indonesis; and (2) the role of Bawaslu can be strengthened in this context. The study concludes that enhancing Bawaslu’s role in election law enforcement can be achieved by granting it comprehensive, one-stop authority. This includes proposing a Bawaslu Bill, establishing a special election court, and improving Bawaslu’s human resource capacity.